Investigating older adults' attitudes towards crisis informatics tools : Opportunities for enhancing community resilience during disasters - Nurul Mubinah, Suhaimi; Zhang, Yixuan; Joseph, Mary Amulya; Kim, Miso; Parker, Andrea Grimes; Griffin, Jacqueline A. (Association for Computing Machinery, 2022)
The world population is projected to rapidly age over the next 30 years. Given the increasing digital technology adoption amongst older adults, researchers have investigated how technology can support aging populations. However, little work has examined how technology can support older adults during crises, despite increasingly common natural disasters, public health emergencies, and other crisis scenarios in which older adults are especially vulnerable. Addressing this gap, we conducted focus groups with older adults residing in coastal locations to examine to what extent they felt technology could support them during emergencies. Our findings characterize participants' desire for tools that enhance community resilience-local knowledge, preparedness, community relationships, and communication, that help communities withstand disasters. Further, older adults' crisis technology preferences were linked to their sense of control, social relationships, and digital readiness. We discuss how a focus on community resilience can yield crisis technologies that more effectively support older adults.